(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2021)
Composites are promising candidates for treating bone defects, but manufacturing of composite scaffolds is challenging. This study aimed to fabricate composite scaffolds based on polycaprolactone (PCL) and doped Hydroxyapatite (HA) via a single step melt extrusion additive manufacturing technique. Starting from the raw powder forms, the printed scaffolds were produced and then characterized for morphology, mechanical behavior and in vitro mineralization. MicroCT revealed the homogenous dispersion of ceramic particles in the PCL matrix. Also, SEM showed the ceramic particles on the surfaces of printed scaffolds. Furthermore, bioactivity assays confirmed the enhanced apatite deposit formation on composite scaffolds compared to PCL alone.